Deep Learning-Based Recommendation System for Breast Cancer Diagnosis - Abdullah, Soona Ahmed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Breast cancer is considered one of the deadliest cancers among females. Despite the advanced achievement in the field of medical imaging analysis, a few early research works proposed semi-automatic machine learning algorithms that were complex and computationally expensive. Recently, developing a system based on deep learning concepts was the center of the attention to analyze mammograms, which is the golden standard imaging technique to diagnose the existence of an abnormality in breast tissues. Systems based on deep learning are still considered to be limited due to insufficient datasets. In this study, numerous experiments were made on small size ROI samples of mammogram images in the CBIS-DDSM dataset to find the best configuration of a pre-trained Convolutional Neural Network with ImageNet dataset. The main training concept is about extracting standard features automatically by striding filters over the input matrix (mammogram). Thus, a larger number of inputs lead to recognize a useful pattern to classify the abnormality. The pre-trained models along with data augmentation algorithms are applied to minimize the dataset challenge in the breast cancer diagnosing field. On the other hand, image preprocessing techniques helped to enhance the image inputs. The study addresses two pre-trained models VGG16 and ResNet50, both were fine-tuned in different depths and hyper-parameters. The experimental results obtained with good performance used a VGG16 pre-trained model after fine-tuning the last fully connected layer. The proposed VGG16 model outperformed other deep learning algorithms with an F1 score and AUC of 82% when classifying the abnormality type into calcification/ mass. The model has also a high score with a mean AUC equal to 0.80 when classifying the mammograms into four classes: benign calcification, malignant calcification, benign mass, and malignant mass. The final application in this study tries to assist radiologists to accomplish more precise decision on the abnormality pathology of breast lesions present in full mammogram images. The application also helps in reducing diagnosing time hence increasing the early detection time. Keywords: CNN, Transfer Learning, Breast Abnormality, Classification, Mammograms, Calcification, Mass.

ÖZ: Göğüs kanseri, kadınlar arasında ölümcül kanserlerden biri olarak kabul edilir. Tıbbi görüntüleme analizi alanındaki gelişmiş başarıya rağmen, birkaç araştırma çalışması, karmaşık ve hesaplama açısından pahalı olan, yarı otomatik makine öğrenim algoritmaları önermişlerdir. Son zamanlarda, derin öğrenme kavramlarına dayalı bir sistem geliştirmek ilgi odağı olmuştur. Bununla birlikte, bu sistemler, çoğunlukla mamografi görüntülerini analiz eder ve meme anormalliğinin varlığını teşhis etmek için altın standart, mevcut veri setlerinin yetersiz olması nedeniyle hala sınırlı olduğu düşünülmektedir. Bu çalışmada, ImageNet veri kümesiyle önceden eğitilmiş evrişimli sinir ağına dayalı bir transfer öğrenme modelinin en iyi modelini bulmak için, CBIS-DDSM veri kümesindeki mamogram görüntülerinin küçük boyutlu ROI örnekleri üzerinde çok sayıda deney yapılmıştır. Eğitim veri seti, giriş matrisi (bir mamogram görüntüsü) üzerinden filtreler ilerletilerek standart özelliklerin otomatik olarak çıkarılmasında kullanılır. Bu nedenle, daha fazla sayıda girdi, anormalliği sınıflandırmak için kullanışlı bir modelin ortaya çıkmasına yol açar. Göğüs kanseri teşhisi alanında veri seti elde etme zorluğunu en aza indirmek için uygulanan veri büyütme algoritmalarıyla birlikte önceden eğitilmiş modellerin kullanımı sağlandı. Öte yandan, görüntü ön işleme teknikleri görüntü girdilerini istenen forma getirmek için uygulandı. Bu çalışmada, önceden eğitilmiş iki ana model senaryosu ele alınmıştır; VGG16 ve ResNet50. Her ikisi de farklı derinliklerde ve hiper parametrelerinde ince ayarlamalar yapılarak uygulanmıştır. Önceden eğitilmiş VGG16 modeli ile, deneysel çalışmalarımız sonucunda, son tam bağlı katmanı üzerinde ince ayarlar yapıldıktan sonra, iyi performans değerleri elde edilmiştir. Önerilen VGG16 modeli, anormallik türünü kalsifikasyon / kütle olarak sınıflandırmasını yaparken, F1 skoru ve AUC değeri %82 olarak elde edilmiş, diğer derin öğrenme algoritmalarından daha iyi performans göstermiştir. Model ayrıca mamogramları dört grupta sınıflandırırken, ortalama AUC değeri %80 olarak hesaplanmış ve yüksek bir performans elde edilmiştir. Önerilen model ile, “iyi huylu kalsifikasyon”, “kötü huylu kalsifikasyon”, “iyi huylu kitle”, ve “kötü huylu kitle” sınıflandırması yapılmıştır. Radyologların meme lezyonlarının anormal patolojisi hakkında daha kesin karar vermelerine yardımcı olmak için nihai bir uygulama yapılmış ve tam mamografi görüntüsü göstermektedir. Uygulama aynı zamanda teşhis süresinin azaltılmasına ve dolayısıyla erken tespit süresinin artmasına da yardımcı olur. Anahtar Kelimeler: CNN, Transfer Öğrenme, Meme Anormalliği, Sınıflandırma, Mamografi, Kalsifikasyon, Kütle.
Master of Science in Computer Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2020. Supervisor: Assoc. Prof. Dr. Duygu Çelik Ertuğrul.
Keywords: Computer Engineering; Cancer--Diagnosis--Data processing; Breast Cancer--Diagnosis--Data processing; Artificial intelligence--Medical applications; Image analysis--Diagnostic imaging - Data processing--Diagnostic imaging--Digital techniques--Computer vision; Image Processing, Computer-Assisted; Optical data processing; Medical informatics--Computational intelligence; CNN; Transfer Learning; Breast Abnormality; Classification; Mammograms; Calcification; Mass